Analysis of the Influence of Financial Literacy, Compulsive Buying, and Income on Debt Behavior - Silaban, Cristin Yeremia; Fachrudin, Khaira Amalia; Irawati, Nisrul; Syahyunan, Syahyunan (Indatu Journal of Management and Accounting, 2024)
Ease of shopping, low self-control, and income have encouraged unhealthy debt behavior in this current era. This research examines factors that encourage debt behavior, such as financial literacy, compulsive buying, and income. The subjects of this study are active undergraduate students at the Faculty of Economics and Business, Universitas Sumatera Utara (USU). This type of research is associated with quantitative data and was conducted at the USU in Medan City from March 2023 to January 2024. The sample used was 528 students, who were selected by random sampling method according to the Slovin formula. The analysis technique used is multiple linear regression analysis. Research results show that partial financial literacy has a negative and significant impact on debt behavior, compulsive buying has a positive and significant impact on debt behavior, and income has a negative and significant impact on debt behavior among active students at the Faculty of Economics and Business, USU. Students should have good financial literacy, minimize compulsive buying, and control themselves in carrying out various transactions adjusted to their income; then, debt behavior will be minimized.